Perawatan Implan Gigi pada Kasus Kehilangan Satu Gigi Posterior secara Subcrestal - Raphael, Alexander; Ariesanti, Yessy (Fakultas Kedokteran Gigi Universitas Trisakti, 2024)
Background: Tooth loss can be replaced with dentures, implant dentures are one of the treatment options that can be chosen because they have a comfort, function, and aesthetics. This case report will explain the procedures for the loss of 1 unit mandibular tooth subcrestally. First year after implant placement, there will be a decrease bone in the implant area 1-1,5 mm and followed by normal decrease of 0.1-0.2 mm each year. Case Report: The patient complained of missing lower left tooth and wanted to have permanent prosthesis. The patient had no systemic disorders and allergies. The patient planned to do implant treatment on tooth 37. There are 2 stages of surgery. Stage one involved the implant placement. Second stage the healing abutment installed. The prosthetic stage monolithic zirconia screw and cement retained prosthesis was used. Conclusion: Dental implant treatment with subcrestal placement is considered to have good results in the long term. In the first year after treatment, the alveolar bone will experience a decrease of 1-1.5 mm in the implant area. In this case, implant placement 1 mm below the bone level will reduce the risk of implant exposure in the long term